Roman public law: concept, content, system and its relevance for modern legal science (Journal of actual problems of jurisprudence, 2021)
This article examines the concept, content and system of Roman public law based on the works of the Italian novelist Antonio Guarino. Despite the fact that Roman public law could not compete with private law in terms of scientific and practical significance, the topic of the Roman state system was studied by many scientists – novelists, among whom the brilliant German historian, novelist Theodor Mommsen, who wrote the fundamental work “Roman state law”, occupies an honorable place. Among the Italian novelists who dealt with issues of Roman public law are Antonio Guarino, Pierangelo Catalano, Bonfante, Orangio Ruiz, De Franchishi. Based on the works of prominent Romanists and on the treatises of Roman lawyers and philosophers who devoted a number of fairly well-known works to Roman public law (such as Cicero’s De legibus de civitate») we will not only try to define and reveal the content of Roman public law, but also answer the question of how relevant the study of Roman public law is for modern legal science and whether it is able to solve practical problems in the field of public administration (no matter how absurd it sounded). Key words: Roman public law, Roman studies, state law, theory of law, Roman law.